Implementasi Sistem Keadilan Bagi Tenaga Kerja Indonesia - Ali Fakhrudin (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
This research is to be able to describe the employment system in Indonesia along with the various inhibiting factors and challenges in the employment system in Indonesia in creating a fair system. The condition of the Islamic and national legal systems in the context of optimizing the role of law is appropriate for both Islamic and national laws to support each other so that local wisdom values ​​are able to provide driving force in efforts to create justice. This research uses a socio-legal research approach, or empirical research (sociological juridical) which is oriented towards formal and substantial findings on the study of the justice system for workers in Indonesia on the process by which law occurs and the operation of law in society. This approach is a combination of legal and social methods. Data analysis was carried out after examining and evaluating the data to determine its validity. After that, the data is grouped into categories or issues/themes according to the research objectives. The results in this study are that the Labor Law Number 13 of 2003 and Law Number 2 of 2004. Apart from still being dominated by the adoption of the Western legal system, the implementation of these rules is also still thick with feudalistic nuances, unequal relations, in where labor is often used as a mere "means of production". In fact, in many cases power relations are still dominant in practice. So that workers feel positioned as a weak party. This is indicated by the relatively high demands of workers regarding guarantees for their life and welfare. Keywords: Justice System; Indonesian workers.